Peripapillary gamma zone pit as dehiscence between Elschnig´s border tissue and Bruch´s membrane with herniation and defect of the retinal nerve fiber layer - Hu, Xinxin; Jonas, Jost B. (BMC ophthalmology, 2016)
Background: The parapapillary gamma zone has recently been defined as the parapapillary region free of Bruch’s membrane. Although it has been reported the presence of defects in peripapillary gamma zone, hitherto undescribed is the herniation of the retinal nerve fiver layer tissue into the peripapillary gamma zone defect with the resulting localized defects in the retinal nerve fiber layer. Case presentation: Ophthalmoscopy in a 36-year-old man revealed a localized defect of the retinal nerve fiber layer associated with a yellowish-gray lesion at the inferior temporal outer margin of a peripapillary gamma zone. Enhanced depth imaging of spectral-domain optical coherence tomography (OCT) showed a dehiscence at the connecting point between the central end of Bruch’s membrane and the peripheral end of the border tissue of Elschnig and Jacoby. Retinal nerve fiber layer tissue was herniated through this defect into a cavitation located in the suprachoroidal space and the space above the cerebrospinal fluid space. At a 2-year follow-up examination, the defect and retinal nerve fiber layer defect appeared unchanged. Conclusion: We present a peripapillary gamma zone pit originating as a dehiscence between Elschnig’s border tissue and Bruch’s membrane and associated with a herniation and defect of the retinal nerve fiber layer and with a suprachoroidal cavitation.
Gesehen am 08.08.2019